A novel Cre‐inducible knock‐in ARL13B‐tRFP fusion cilium reporter. Issue 11 (13th October 2017) - Schmitz, Felizitas; Burtscher, Ingo; Stauber, Michael; Gossler, Achim; Lickert, Heiko
Summary: Cilia play a major role in the regulation of numerous signaling pathways and are essential for embryonic development. Mutations in genes affecting ciliary function can cause a variety of diseases in humans summarized as ciliopathies. To facilitate the detection and visualization of cilia in a temporal and spatial manner in mouse tissues, we generated a Cre‐inducible cilium‐specific reporter mouse line expressing an ARL13B‐tRFP fusion protein driven by a CMV enhancer/chicken β actin promotor (pCAG) from the Hprt locus. We detected bright and specific ciliary signals by immunostainings of various mono‐ and multiciliated tissues and by time‐lapse live‐cell analysis of cultured embryos and organ explant cultures. Additionally, we monitored cilium assembly and disassembly in embryonic fibroblast cells using live‐cell imaging. Thus, the ARL13B‐tRFP reporter mouse strain is a valuable tool for the investigation of ciliary structure and function in a tissue‐specific manner to understand processes, such as ciliary protein trafficking or cilium‐dependent signaling in vitro and in vivo .